The rural school in Italy between the 19th and the 20th century - Montecchi, Luca (Historia y Memoria de la Educación, 2018)
The aim of this work is to trace the historical events surrounding primary education for Italian children between the Unification of Italy and the fall of Fascism (1861-1943). We focus particularly on the continuity and the changes in school policy promoted by the Italian government in relation to rural schools, offering an analysis, from an institutional point of view, of the evolution of the legislation and of the history of the state and private institutions in charge of organizing schools for young farmers between the half of the 19th and of the 20th century